The Effect of Zataria multiflora Boiss. Mouthwash on the Oral Microbial Load in Patients under Mechanical Ventilation: A Randomized Controlled Trial - Zahra Gholami; Mansour Dianati; Mahboobeh Maghami; Mohammad Reza Afazel; Ismail Azizi-Fini (Tehran University of Medical Sciences, 2022)
This study aimed to examine the effect of Zataria multiflora Boiss. mouthwash on the microbial load of the oral cavity in patients under mechanical ventilation. This randomized controlled trial was conducted in 2019 on patients under mechanical ventilation. Sampling was performed using the consecutive method. Using a block randomization method, 90 patients were allocated to three equal groups of 30 to receive mouth care using chlorhexidine, Z. multiflora, or normal saline. Mouthwash was used three times a day for a week. Eight hours before and after the intervention, sterile samples of saliva were collected and cultured in the laboratory. Chi-square, Fisher's exact test, paired t and McNemar's tests, and analysis of variance were used to analyze the data. After the interventions, a significant difference in the microbial load was found between the three groups (P < 0.021). The Tukey post hoc test showed a significant difference between the group treated with Z. multiflora and those who received chlorhexidine (P value = 0.016). The frequency of patients with positive cultures was lower in the group treated with Z. multiflora and the differences were statistically significant in terms of Acinetobacter (P = 0.01) and Klebsiella pneumonia (P = 0.02). Z. multiflora mouthwash was effective in decreasing the microbial load of the oral cavity. This mouthwash can be used to reduce the microbial load of the oral cavity in patients under mechanical ventilation and reduce the risk of ventilator-associated pneumonia.